2017
DOI: 10.1016/j.jmb.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Redirecting SR Protein Nuclear Trafficking through an Allosteric Platform

Abstract: Although phosphorylation directs serine-arginine (SR) proteins from nuclear storage speckles to the nucleoplasm for splicing function, dephosphorylation paradoxically induces similar movement raising the question of how such chemical modifications are balanced in these essential splicing factors. In this new study we investigated the interaction of protein phosphatase 1 (PP1) with the SR protein SRSF1 to understand the foundation of these opposing effects in the nucleus. We found that RNA recognition motif 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 68 publications
3
25
0
Order By: Relevance
“…These results are in keeping with a prior report (18) and show that the apparent binding affinity of RRM1 is at least 40-fold higher than that for RRM2. Because RRM1 is a noncompetitive inhibitor with respect to PNPP, app K I is also equivalent to the true K I (18). However, because this assay depends on functional changes in PP1 and RRM2 might bind to PP1 but not influence catalysis, we decided to perform a competition experiment.…”
Section: Pp1 Binds Selectively To Rrm1supporting
confidence: 93%
See 2 more Smart Citations
“…These results are in keeping with a prior report (18) and show that the apparent binding affinity of RRM1 is at least 40-fold higher than that for RRM2. Because RRM1 is a noncompetitive inhibitor with respect to PNPP, app K I is also equivalent to the true K I (18). However, because this assay depends on functional changes in PP1 and RRM2 might bind to PP1 but not influence catalysis, we decided to perform a competition experiment.…”
Section: Pp1 Binds Selectively To Rrm1supporting
confidence: 93%
“…Because we showed previously that RRM1 in SRSF1 binds and down-regulates PP1, we wished to identify unique residues in this domain that interact with this phosphatase. We first verified previous findings that PP1 binds selectively to RRM1 in SRSF1 (18). In pulldown assays, we showed that GST-PP1 interacts with His-tagged RRM1 but not with His-tagged RRM2 ( Fig.…”
Section: Pp1 Binds Selectively To Rrm1supporting
confidence: 88%
See 1 more Smart Citation
“…regulates the interaction and dephosphorylation activity of PP1␥ (41). Because SRSF3 lacks both interaction due to the absence of a pseudo-RRM and the conserved RVXF PP1-binding sequence, we speculated that the hypophosphorylation state of SRSF3 is the result of increased sensitivity to dephosphorylation by phosphatases.…”
Section: Phosphorylation Mechanisms Of Sr Proteinsmentioning
confidence: 99%
“…The interaction between an acidic cluster within the pseudo-RRM and the RS domain, in particular, prevents dephosphorylation of the RS domain by phosphatases, suggesting a novel role of SR protein pseudo-RRM in vivo. The same research team later found that the canonical RRM of SRSF1, which contains a putative PP1-binding motif, also plays a regulatory role during its RS domain dephosphorylation by interacting with and allosterically inhibiting PP1␥ (41). SRSF3 does not contain either structural element to protect its RS domain from dephosphorylation.…”
Section: Phosphorylation Mechanisms Of Sr Proteinsmentioning
confidence: 99%